2012
DOI: 10.1353/hpu.2012.0109
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Provider Factors Associated with Colorectal Cancer Screening in Safety Net Clinics Serving Low-income, Urban Immigrant Latinos

Abstract: Background Latinos have lower colorectal cancer screening rates than Whites. Methods We reviewed a random sample of charts between July 2009 and February 2010 of safety-net clinic of 840 immigrants (50 years and older) from Central and South America receiving care. Logistic regression evaluated associations of ever vs. never screening, patient and physician factors. Results Ever screening rates were 24.5%, and only 17% of charts noted a physician screening recommendation. However, the odds of screening wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…These studies showed that PCP visits [4][5][6][7][8] and physician recommendation were strong predictors of prevalent CRC screening (mostly with colonoscopy). 2,6,8 Our study extends prior work by demonstrating an independent association between prior primary care visits and subsequent Bincident^CRC screening, including outreach screening not linked directly to the primary care visit. This work is particularly important in the modern era, where large private and public health systems have extensive CRC screening outreach programs and are promoting annual FIT/FOBT as a dominant strategy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies showed that PCP visits [4][5][6][7][8] and physician recommendation were strong predictors of prevalent CRC screening (mostly with colonoscopy). 2,6,8 Our study extends prior work by demonstrating an independent association between prior primary care visits and subsequent Bincident^CRC screening, including outreach screening not linked directly to the primary care visit. This work is particularly important in the modern era, where large private and public health systems have extensive CRC screening outreach programs and are promoting annual FIT/FOBT as a dominant strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, patients who are more prevention-oriented may be both more motivated to follow up abnormal screening tests and more engaged in primary care. Previous research in primary care settings 5,6,28 and the general population 4,8 that have examined predictors of CRC screening have focused primarily on Bprevalent^screening (having ever been screened) and in settings where colonoscopy (which offers 10 years of protection) was the predominant screening modality. These studies showed that PCP visits [4][5][6][7][8] and physician recommendation were strong predictors of prevalent CRC screening (mostly with colonoscopy).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, CNP reports described culturally tailored interventions that resulted in reduced tobacco use among Asian immigrants 46 and Native Hawaiians. 47 They described CBPR projects that attracted rural dwelling adults to cancer screening for the first time 40 ; increased breast and cervical cancer screening among Vietnamese, Hmong, Micronesian, Hispanics, and African-American women 17,23,48–50 ; increased colorectal cancer screening among Chinese Americans, 44 Hispanics, 51,52 and African Americans 53 ; increased Pap test follow-up among American Indian women 54 ; increased hepatitis B immunization among Asian Americans 55 ; increased prostate cancer screening among African Americans 56,57 ; and increased minority participation in clinical trials. 58,59 …”
Section: Resultsmentioning
confidence: 99%